2005
DOI: 10.1074/jbc.m504460200
|View full text |Cite
|
Sign up to set email alerts
|

Human Acyl-CoA Dehydrogenase-9 Plays a Novel Role in the Mitochondrial β-Oxidation of Unsaturated Fatty Acids

Abstract: Unsaturated fatty acids play an important role in the prevention of human diseases such as diabetes, obesity, cancer, and neurodegeneration. However, their oxidation in vivo by acyl-CoA dehydrogenases (ACADs) that catalyze the first step of each cycle of mitochondrial fatty acid ␤-oxidation is not entirely understood. Recently, a novel ACAD (ACAD-9) of unknown function that is highly homologous to human very-long-chain acyl-CoA dehydrogenase was identified by large-scale random sequencing. To characterize its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
94
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 57 publications
1
94
0
Order By: Relevance
“…At least nine members of this family have been described (Ensenauer et al, 2005;Ikeda et al, 1985). Substrate specificity is the most important characteristic to define the members of the ACADS family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least nine members of this family have been described (Ensenauer et al, 2005;Ikeda et al, 1985). Substrate specificity is the most important characteristic to define the members of the ACADS family.…”
Section: Discussionmentioning
confidence: 99%
“…ACADSB is expressed in adipose tissue, lymphatic reticulum, breast tissue, muscle tissue and rumen. Acyl-CoA dehydrogenases with specificity for different chain lengths of fatty acids in the mitochondria carry out the first committed step of β-oxidation reaction (Ensenauer et al, 2005). Studies revealed that ACADSB gene single-nucleotide polymorphisms are associated with hyperlipidemia in humans (Kamide et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…There are nine members of this family, five of which are involved in the mitochondrial fatty-acid -oxidation process: short-chain, medium-chain, long-chain and verylong-chain acyl-CoA dehydrogenases (SCAD, MCAD, LCAD and VLCAD-1, respectively) and the recently reported very-long-chain acyl-CoA dehydrogenase ACAD-9 (VLCAD-2) (Zhang et al, 2002;Ensenauer et al, 2005;Kim & Miura, 2004). The other four members are involved in the amino-acid oxidation pathway and comprise iso(3)valeryl-CoA dehydrogenase (I3VD) for leucine, iso(2)valerylCoA dehydrogenase (I2VD) for isoleucine, isobutyryl-CoA dehydrogenase (IBD) for valine and glutaryl-CoA dehydrogenase (GD) for lysine and tryptophan (Kim & Miura, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Acyl-CoA dehydrogenase catalyzes the first step of fatty acid b-oxidation in the(VLCAD) are homodimers associated with the inner mitochondrial membrane (Ensenauer et al 2005). ACAD9 shares 47% amino acid identity and 65% amino acid similarity with VLCAD, which is encoded by the gene ACADVL (Zhang et al 2002); this could be explained by ACADVL gene duplication.…”
Section: Introductionmentioning
confidence: 99%
“…This structural difference may underlie the distinct roles of these enzymes. In fact, although ACAD9 conserves its b-oxidation activity (Ensenauer et al 2005), VLCAD has a significant higher activity level in degrading unsaturated long-chain fatty acids. It has been shown recently that ACAD9 plays a pivotal role in the assembly of chain respiratory complex I (Nouws et al 2014a, b).…”
Section: Introductionmentioning
confidence: 99%